(untitled) (Ameghiniana, 2013)
The present paper intends to confirm, disconfirm or to fit previous hypothesis or to propose new hypothesis about the evolution of marine and continental temperatures in the Austral portion of South America during the Cenozoic. To attain this purpose paleoichthyological evidences are employed. Related ecological and biogeographical aspects of fossil and recent fishes are discussed. Some of the conclusions are: Some fishes probably have changed its ecological characteristics during the Cenozoic, The fishes do not falsify previous hypothesis about the ’Salamanquian Stage. The faunistic change that occurs -ín La Meseta Formation (Seymour Island), would be related with the establishment of the Circum Antarctic Current. There are evidences that in the North Western Area of Argentina the environmental conditions were very different from those that exist in the Present until, at least, the Anta Formation deposition. The fishes of the lower levels of the "Patagoniano" from the Chubut river area correspond to moderately warm temperate seas. On the other hand, those that occur in the Entrerriano and/or Paraniano Stage in Entre Ríos correspond to seas of higher temperatures. It is possible that the South American fishes did not migrate to Australia via Antarctica due to the existence of a cold temperate climate in some areas of this continent since the late Cretaceous.